2020
DOI: 10.1007/s10120-020-01094-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective sensitivity of EZH2 inhibitors based on synthetic lethality in ARID1A-deficient gastric cancer

Abstract: Background AT-rich interactive domain 1A (ARID1A) is a tumor suppressor gene that is frequently mutated in gastric cancer (GC). Although ARID1A mutations are not a druggable target for conventional treatments, novel therapeutic strategies based on a synthetic lethal approach are effective for ARID1A-deficient cancers. The histone methyltransferase EZH2 acts in a synthetic lethal manner in ARID1A-mutated ovarian cancer, although its role in GC remains unknown. Methods The selective sensitivity of the EZH2 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
2
19
0
2
Order By: Relevance
“…For ARID1A-deficient cancer cells, Ogiwara et al [40] showed that they express low levels of gluthation (GSH), which makes them specifically vulnerable to inhibition of the GSH metabolic pathway. Additionally, increased sensitivity of ARID1A-deficient cancer cells to treatment with small molecule inhibitor of the PI3K/AKT pathway or selective sensitivity of EZH2 inhibitors against ARID1A-deficient gastric cancer could be demonstrated [41][42][43]. EZH2 inhibitor tazemostat is currently investigated in ongoing clinical trials including SMARCA4-negative solid tumors [18].…”
Section: Discussionmentioning
confidence: 99%
“…For ARID1A-deficient cancer cells, Ogiwara et al [40] showed that they express low levels of gluthation (GSH), which makes them specifically vulnerable to inhibition of the GSH metabolic pathway. Additionally, increased sensitivity of ARID1A-deficient cancer cells to treatment with small molecule inhibitor of the PI3K/AKT pathway or selective sensitivity of EZH2 inhibitors against ARID1A-deficient gastric cancer could be demonstrated [41][42][43]. EZH2 inhibitor tazemostat is currently investigated in ongoing clinical trials including SMARCA4-negative solid tumors [18].…”
Section: Discussionmentioning
confidence: 99%
“…ARID1A affects the process of EMT in multiple cancers, such as gastric cancer, neuroblastoma, and liver cancer ( 37 , 96 98 ). In gastric cancer cell lines, the silence of ARID1A increases the expression of vimentin and N-cadherin and promotes local lymph node metastasis and distant metastasis ( 96 , 97 ). Meanwhile, knockdown of ARID1A in neuroblastoma SK-N-SH cells is found to raise the expression of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) and lessens the expression of E-cadherin, which ultimately leads to the enhancement of neuroblastoma invasion and migration ( 98 ), and the upregulated levels of MMP-9 upon ARID1A inhibition is recently shown to be due to the strengthened MMP-9 protein stability in JEG-3 choriocarcinoma cell line ( 75 ).…”
Section: Underlying Mechanisms Of Tumor Suppression By Arid1amentioning
confidence: 99%
“…Immunohistochemical staining and evaluation. IHC staining of formalin-fixed, paraffin-embedded (FFPE) histological sections (4 μm thick) was performed using a polymer peroxidase method, as previously performed 19,32 . Briefly, after deparaffinization and rehydration, the sections were treated with 0.3% hydrogen peroxide in methanol for 30 min to block endogenous peroxidase activity.…”
Section: Author Contributionsmentioning
confidence: 99%